Analysis of Fractional-Order Models Of Polyaniline Doped Polyacrylonitrile Fibres Impedances’ (PAN/PANI) - Rybicki, Tomasz (Sci Rep, 2020)
The paper describes the use of electrical impedance spectroscopy (EIS) for characterizing the impedance of polyaniline doped polyacrylonitrile fibres. The electrical impedance of fibres samples was measured by means of high impedance analyser and modeled by four types of models: Debye, Cole-Cole, Davidson-Cole and Havriliak-Negami. The fitting errors are presented for all model types. The model parameters are correlated with chemical substances additives and processing which were used during the fibres production. The presented results show that the fractional-order models reflect properly the impedance spectra of fibres samples.